DETERMINING THE BLOOD ALCOHOL LEVEL OR THE PRESENCE OF PSYCHOACTIVE SUBSTANCES AMONG RAILWAY STAFF - Georgian RĂDĂȘANU (Challenges of the Knowledge Society)
This article aims to analyse the concrete way in which the concentration of alcohol in the blood or the presence of psychoactive substances among the railway staff is determined, in the wider context of the analysis, within a separate scientific approach, of the railway crime regarding the fulfillment of the duties of service under the influence of alcoholic beverages or other substances, provided by art. 331 para. (2) CP. Following the examination of the Order of the Minister of Transport and Telecommunications no. 855/1986, we will be able to observe the causes for which, in order to prove the concentration of alcohol or the presence of psychoactive substances among railway personnel with duties regarding the safety of railway traffic, the judicial bodies end up applying, by extension, the provisions of a normative act aimed at judicial probation in the case of persons involved in events or circumstances related to road traffic. In this context, this approach seeks to raise the issue of the need for a clear and predictable infralegal regulation, which takes into account the specificity and the current realities in the railway and medical fields, in order to provide real support for the judicial bodies regarding the proof of the found railway crime within the Criminal Code.